2018
DOI: 10.1021/acs.jpclett.8b00600
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Efficiency Roll-Off and Enhanced Stability in Perovskite Light-Emitting Diodes with Multiple Quantum Wells

Abstract: Mixed-formamidinium (FA) and -cesium (Cs) cations were used to fabricate multiple quantum well (MQW) perovskite light-emitting diodes (PeLEDs). The partial substitution of FA with Cs facilitates the formation of wider quantum wells, which can effectively reduce efficiency roll-off by suppressing Auger recombination. The device has a peak external quantum efficiency (EQE) of 7.8% at a current density of 125 mA cm, maintaining an EQE of ∼6.6% at a high current density of 500 mA cm. Due to the improved stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 25 publications
(64 reference statements)
2
69
0
Order By: Relevance
“…Xie et al demonstrated that the addition of FA + into CsPbBr 3 resulted in an enhanced operational lifetime in perovskite LEDs, which was attributed to a reduced trap density [31]. Yang et al achieved a more significant operational stability improvement with a partial substitution of Cs + in a FA + based perovskite LED [28]. The mixed-cation perovskite LED had a lifetime of ∼31 h in contrast to ∼1 h for the device without Cs + addition under a constant current density of 10 mA cm −2 .…”
Section: A-site Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Xie et al demonstrated that the addition of FA + into CsPbBr 3 resulted in an enhanced operational lifetime in perovskite LEDs, which was attributed to a reduced trap density [31]. Yang et al achieved a more significant operational stability improvement with a partial substitution of Cs + in a FA + based perovskite LED [28]. The mixed-cation perovskite LED had a lifetime of ∼31 h in contrast to ∼1 h for the device without Cs + addition under a constant current density of 10 mA cm −2 .…”
Section: A-site Engineeringmentioning
confidence: 99%
“…However, due to the low field present during operation, ion migration does not appear to be a severe problem affecting the operational lifetime of perovskite PVs [27]. On the contrary, it is not uncommon to see a perovskite LED degrades to half of their initial efficiency within hours [16,18,28,29] or even minutes [17,[30][31][32][33][34] due to ion migration under an applied electric field. In addition, perovskite can undergo electrochemical reactions driven by charge injection, leading to interfacial degradation and perovskite decomposition [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe this is probably resulting from two reasons: 1) a slow trap‐filling process by the injected carriers and/or ionic motion; 2) a slow internal field‐redistribution due to local ionic motion of excess ions under external electric field . The device EQE EL decays to half of the initial value after ≈96 h of continuous operation at a given current density of 200 mA cm −2 , creating a new record of operation lifetime for perovskite LEDs, and even better than the best performing near infrared organic LEDs . For a higher injection current density of 1000 mA cm −2 , the operation lifetime of quasi‐2D perovskite LED still reaches an impressed 5.35 h. Our results suggest that the good stability of the LED devices can be attributed to the intrinsic stability of quasi‐2D perovskite films with high crystallinity and a low level of defects.…”
mentioning
confidence: 99%
“…b,c) External quantum efficiency (EQE (%)) and luminescence of the best reported LEDs plotted as a function of injection current density. The data are plotted using the reported EQE values, and luminescence for red/NIR and green, blue, and orange PeLEDs. For details of each device and its performance parameters, refer to Table .…”
Section: Introductionmentioning
confidence: 99%